The Effect of Combination Massage Frirage and Stretching on Increased The Range of Motion Shoulder Injury in Patients of Mco Yurigi - Al Jabar, M Irsyad; Sugiarto, Sugiarto; Sumartiningsih, Sri; Setiowati, Anies (Journal of Physical Education and Sports, 2023)
Limited range of motion of the shoulder joint due to injury can limit a person's activity. The purpose of this study was to determine the effect of a combination of frirage massage and stretching on increasing the range of motion of shoulder injuries in MCO Yurigi patients by providing treatment four times a meeting and eight times a meeting, and providing information to choose the right method to accelerate and increase the range of motion of shoulder injuries. This study used a quasi-experiment "one group pretest posttest" design. The sampling technique used purposive sampling technique with a population of 20 people and obtained a sample of 12 people. The data analysis technique uses one way anova with the SPSS version 26 programme. The research variables are 1) independent variable: combination of massage frirage and stretching, 2) dependent variable: range of motion of the shoulder joint. The results of this study showed an increase in the average value of range of motion with treatment for four meetings, namely flexion 24.5°, extension 9.5°, abduction 22.9°, adduction 10°, medial rotation19.1°, lateral rotation 19.1° and treatment for eight meetings, namely flexion 46.6°, extension 19.1°, abduction 46.6°, adduction 19.1°, medial rotation 40°, lateral rotation 38.3°. The conclusion of this study is that the combination of massage frirage and stretching has an influence on increasing the range of motion of the shoulder joint by giving treatment four times and eight meetings.